Analisis Ekonomi Politik Lembaga PJPH, LPH, Dan MUI Terhadap Kebijakan Kewajiban Sertifikasi Halal Di Indonesia - Dita Anjani; Riyati Husnul Hotimah; Saviola Oryza Sativa; Dzulfa Fikriyyah Syifa; Ahmad Iqbal Jaza (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Introduction: The Indonesian Ulema Council (MUI), the Halal Product Guarantee Organizing Agency (BPJPH), and the Halal Inspection Institute (LPH) have been formed by the government through its ministries to ensure that the implementation of the Halal Product Guarantee runs smoothly since regulations related to this matter were issued in 2014 until it comes into effect in 2019. This research aims to provide a general overview of the political economic situation faced by BPJPH, LPH, and MUI organizations when implementing policies that require halal certification. Research Methods: This research data was collected from literature relevant to the research problem using qualitative methods and library research. Result: According to the findings of this study, halal product certification policies in Indonesia are still not ideal. Due to the lack of recognized Halal Inspection Institutions (LPH),effectiveness, equity and reach are still not adequately met. However, over time, the government has been quite effective in responding to requests for halal certificate subsidies and achieving its targets. The hope is that business actors can maximize the opportunity for free halal certification, before it becomes payable.